2014
DOI: 10.1590/s0100-29452014000500006
|View full text |Cite
|
Sign up to set email alerts
|

Principais doenças de Anonáceas no Brasil: descrição e controle

Abstract: 3RESUMO-Várias doenças podem afetar folhas, caules, flores e frutos de gravioleira, pinheira e atemoia em diferentes estádios de seus desenvolvimentos. Geralmente, as doenças mais importantes são causadas por fungos durante o florescimento e a frutificação. Também podem ocorrer murchas ou podridões de raízes, causadas por nematoides e patógenos do solo. A antracnose (Colletotrichum gloeosporioides), murcha ou podridões de raízes (Rhizoctonia solani, Cylindrocladium clavatum, Phytophthora sp., Pythium sp., Phyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…Studies have shown that certain fungi, such as Lasiodiplodia theobromae, an opportunistic or secondary pathogen, have been a problem for production in tropical regions. This pathogen, when it gets inside the tissues of the plant, causes the death of the individual or fall of flowers and fruits of diverse species of economic interest (Junqueira & Junqueira, 2014).…”
Section: Palavras-chavementioning
confidence: 99%
“…Studies have shown that certain fungi, such as Lasiodiplodia theobromae, an opportunistic or secondary pathogen, have been a problem for production in tropical regions. This pathogen, when it gets inside the tissues of the plant, causes the death of the individual or fall of flowers and fruits of diverse species of economic interest (Junqueira & Junqueira, 2014).…”
Section: Palavras-chavementioning
confidence: 99%
“…In the past, the dieback of Annonaceae was associated with L. theobromae only (Ponte, ; Lopez, ; Junqueira & Junqueira, ). However, in this study, through combined phylogenetic analysis of ITS, TEF‐1α , TUB2 and RPB2 sequences, eight species of Botryosphaeriaceae were identified associated with dieback on A. muricata , A. squamosa , atemoya ( A. cherimola × A. squamosa ), A. leptopetala and with fruit rot in A. crassiflora.…”
Section: Discussionmentioning
confidence: 99%
“…Several diseases and pathogens have been reported on Annonaceae in Brazil (Lopez, ; Junqueira & Junqueira, ). However, despite the great economic importance and the expansion of areas cultivated with these fruit crops in Brazil, there is a lack of research on disease diagnostics in these crops.…”
Section: Introductionmentioning
confidence: 99%
“…2 The disease can be found in orchards of the species Passiflora edulis f. flavicarpa, P. alata, P. cincinata, P. nitida, P. quadrangularis, P. amethystina, P. setacea and P. edulis f. edulis. 3 Xanthomonas axonopodis pv. passiflorae is a gram-negative, strict aerobic bacterium, with mucoid, convex, bright, yellow-colored colonies.…”
Section: Introductionmentioning
confidence: 99%